The Effect of Using Scaffolding Strategies on EFL Students’ Reading Comprehension Achievement - Abdul-Majeed, Maysaa Rasheed; Muhammad, Narmeen Mahmood (Al-Adab Journal, 2015)
Scaffolding is a process that supports and improves the performance of students before, during, and after reading. Graphic organizers, pictures, and charts can all serve as scaffolding tools. All of them can help, guide and shape students’ thinking when they apply them, i.e., students can discuss, write an essay, or use them with the difficult reading texts and new challenging information. This study is an attempt to investigate the effect of using scaffolding strategies on EFL students’ achievement in reading comprehension. To fulfil the aims of the study, the researchers have adopted two null hypotheses: first, there is no statistically significant difference between the achievement mean scores of students who practice scaffolding strategies and that of students who do not practice them. Second, there is no statistically significant difference between the experimental group students’ achievement mean scores in the pre and posttests of reading comprehension. To achieve the aims of the study, a six-week experiment was conducted using pretest-posttest non-equivalent groups design. Two groups of 22 students each were selected from the population of second year students (N=123)/College of Education for Women/Department of English during the academic year (2013-2014). One group was selected as the experimental group that was taught reading comprehension using scaffolding strategies and other group was selected as the control group that was taught according to the lecture method. The students of both groups were exposed to pre and posttests. Using the t-test for two independent samples, it is found that there is a statistically significant difference in favour of the experimental group. This indicates that teaching by scaffolding strategies is more effective than the presentation practice production teaching or the Lecture Method teaching. Conclusions, recommendations and suggestions for further studies are put forward.